A Preliminary Study of the Cross-Reactivity of Canine MAGE-A with Hominid Monoclonal Antibody 6C1 in Canine Mammary Gland Tumors: An Attractive Target for Cancer Diagnostic, Prognostic and Immunotherapeutic Development in Dogs - Wanwisa Srisawat; Boondarika Nambooppha; Kidsadagon Pringproa; Atigan Thongtharb; Worapat Prachasilchai; Nattawooti Sthitmatee (Veterinary Sciences, 2020)
Melanoma-associated antigen-A (MAGE-A), a family of cancer/testis antigens, has been recognized as a potential target molecule for cancer immunotherapy. However, there has been very little information available with regard to this antigen in dogs. This study aimed to investigate the expression of MAGE-A in canine mammary gland tumors (CMTs) using immunohistochemistry and immunoblotting with human monoclonal MAGE-A antibody 6C1. The present study has provided evidence of cross-reactivity of the canine MAGE-A expression with the human MAGE-A antibody in CMTs. The MAGE-A antigens were expressed in moderate- and high-grade malignant CMTs (22.22%, 2/9), but no expression was observed in benign CMTs. The immunohistochemical staining of canine MAGE antigen in CMT cells showed nuclear and nuclear–cytoplasmic expression patterns that may be involved with the mitotic cell division of tumor cells. Molecular weights of the canine MAGE-A antigen presented in this study were approximately 42–62 kDa, which were close to those of other previous studies involving humans and dogs. The findings on this protein in CMTs could supply valuable oncological knowledge for the development of novel diagnostic, prognostic and immunotherapeutic tumor markers in veterinary medicine.